Pré-condicionamento com oxigenoterapia hiperbárica em gatas submetidas a ovariohisterectomia eletiva videoassistida: temperatura corpórea, analgesia e biomarcadores oxidativos - Martins, Leticia Reginato (2022)
This study aimed to evaluate the influence of hiperbaric oxygen therapy (HBOT) in cats undergoing ovariohysterectomy (OHE) regarding postoperative pain stimulus, central temperature (CT), peripheral (PT) and the variation between central temperature and peripheral temperature (ΔTc-p), in addition to the HBOT’s influence in oxidative stress biomarkers. For such matter, 45 female cats were divided randomly in: Hiperbaric Group (HG): (n=15) 45 minutes of HBOT under the pressure of 2 absolute atmospheric pressure (AAP) before video assisted OHE; Control Hiperbaric Group (CHG): (n=15) same HBOT regimen, without surgical procedure; Sham Group (SHAM) (n=15) submitted only to elective OHE. The first article evaluated the effects of the treatment with HBOT before the surgery on temperature and post operatory pain. For analgesic evaluation, was used the Feline Grimace Scale (FGS) and the Multidimensional UNESP – Botucatu Scale (UNESPS) in predetermined times. Five received analgesic rescue, four of them belonging to SHAM and one to HG. Final CTs of groups SHAM and HG were smaller than the initial CTs, but there was no difference between the groups. ΔCT-P showed treatment effect (HG x SHAM) (p<0,038) and time (initial x final) (p<0,0001). HG and SHAM presented difference in initial and final ΔCT-P (<0,001 for both). It was concluded that there was no HBOT’s positive influence on post operative pain. There was no difference between CT, PT or ΔTc-p in animals submitted or not to HBOT. The temperature reduction in healthy cats after HBOT had no clinic significance. The second article aimed to determinate how pre surgical HBOT changes oxidative stress biomarkers during video assisted OHE, for such matter it was quantified serum values of Thiobarbituric Acid Reactive Substances (TBARS), Reactive Oxygen Species (ROS), Superoxide Dismutase (SOD), Catalase (CAT), Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in all the 45 selected cats. Blood samples were obtained to SHAM and HG groups: T1 = immediately before the beginning of the surgery, during anesthetic stabilization; T2 = in the extubation moment; T3 = 24 hours after the end of the surgical procedure. To the CHG the collections were done in T1 = after sedation; T2 = after reversion (30 minutes after) and T3 = 24 hours after reversion. There was no difference regarding the serum generation of ROS, AChE or BChE. There was a rise in TBARS in T3 SHAM when compared to HG (p=0,043). There was an activity reduction in CAT in T2 and T3 SHAM in relation to T1 SHAM (p=0,012 and p<0,001, respectively). T2 SHAM presented less CAT activity in comparison to T2 CHG (p=0,05). Also, T3 SHAM was smaller than T3 HG (p=0,030) and T3 CHG (p=0,050). There was a SOD’s reduction in T2 SHAM in comparison to T3 HG (p=0,039) and T3 CHG (p=0,019). This study showed that HBOT seems to have a favorable influence at oxidative stress reduction and at serum levels of these biomarkers.